Class Pet Mess! - Gutman, Dan; Paillot, Jim (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2017)
Alexia's delighted when Mr. Cooper brings in Bob, a hognose snake, as class pet, but when Bob keels over, is Andrea's toy poodle or Alexia's neglect to blame?
Keywords: Schools -- Juvenile fiction; Hognose snakes -- Juvenile fiction; Snakes as pets -- Juvenile fiction; Pets -- Juvenile fiction; Schools -- Fiction; Hognose snakes -- Fiction; Snakes as pets -- Fiction; Pets -- Fiction; Humorous Stories; JUVENILE FICTION / Readers / Beginner; JUVENILE FICTION / School & Education; JUVENILE FICTION / Humorous Stories